Common Freshwater Fish Parasites Pictorial Guide: Acanthocephalans, Cestodes, Leeches, & Pentastomes - Deborah B. Pouder; Eric W. Curtis; Roy P. Yanong (EDIS)
This publication is one in a series of pictorial guides that is designed to assist in the identification of common freshwater fish parasites. The information provided in this guide is not intended to be a complete, detailed description of each parasite or parasite group and its characteristics but rather is intended to assist in the visual identification of some of the most common species or groups of parasites seen in freshwater fish. For further information on each parasite, refer to publications in the “Recommended Reading” and “Reference” sections. This document is Fact Sheet FA-114, one of a series from the Tropical Aquaculture Laboratory, Department of Fisheries and Aquatic Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: July 2005.